A kind of hole transport layer-free perovskite solar cell based on CuSeCN additive and preparation method

CN119836206BActive Publication Date: 2026-10-09东方电气长三角(杭州)创新研究院有限公司
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411772040.8
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-12-04
Publication Date
2026-10-09
Estimated Expiration
2044-12-04

AI Technical Summary

Technical Problem

[0004]在无空穴传输层的倒置结构钙钛矿电池中,通常在钙钛矿前驱体溶液中添加2,3,5,6-四氟-7,7,8,8-四氰基对醌二甲烷、氟化(四芳基苯并[1,2-b:4,5-b']二吡咯-1,5-二亚基)二烷磺酸盐、[4-(3,6-二甲基-9H-咔唑-9-基)丁基]膦酸等p型添加剂来去除空穴传输层沉积步骤,目的是修饰透明导电氧化物/钙钛矿界面的能级排列,但这些无空穴传输层钙钛矿电池的效率和稳定性远落后于常规结构电池

Benefits of technology

[0022]1. In this invention, CuSeCN is added to the perovskite precursor solution. On the one hand, SeCN... - and Pb 2+ The strong coordination between the perovskite precursors induces micro-clustering, promoting heterogeneous nucleation and preferred orientation growth of the perovskite crystals, leading to an increase in the average grain size of the perovskite film. On the other hand, selenium and copper atoms in CuSeCN interact with uncoordinated Pb atoms on the surface. 2+ and the suspended I - Strong bonding forms a local hole-collecting contact structure with good passivation effect, reducing non-radiative recombination, inhibiting perovskite phase separation, and enhancing the chemical structural stability of perovskite films.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119836206B_ABST
    Figure CN119836206B_ABST
Patent Text Reader

Abstract

The application discloses a kind of based on CuSeCN additive's no hole transport layer perovskite solar cell and preparation method, the perovskite solar cell from bottom to top is transparent conductive substrate layer, perovskite light-absorbing layer, electron transport layer, interface buffer layer and electrode layer, wherein perovskite light-absorbing layer contains CuSeCN additive.The application effectively p-type doped to lower interface perovskite film using CuSeCN additive, SeCN ‑ With uncoordinated Pb 2+ Strong bond effect is formed at perovskite film grain boundary, which acts as perovskite electron acceptor, realizing the transformation of bottom perovskite from n-type to p-type conductivity.Meanwhile, the introduction of CuSeCN effectively regulates perovskite crystallization kinetics, increases perovskite grain size, releases the tensile stress of bottom perovskite lattice, forms low defect state density charge transport interface, realizes high-efficiency and stable no hole transport layer perovskite cell, greatly promotes the industrialization process of perovskite solar cell.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of solar cell technology, and in particular to a perovskite solar cell without a hole transport layer based on CuSeCN additive and its preparation method. Background Technology

[0002] Organic-inorganic hybrid perovskite materials have attracted the attention of many researchers due to their excellent photoelectric properties, low cost, and wide availability. The photoelectric conversion efficiency of perovskite solar cells has soared from 3.8% in 2009 to 26.7% in 2024, approaching the level of crystalline silicon solar cells on the market. They are considered to be the third generation of solar cells with the greatest commercial potential.

[0003] However, the fabrication process for high-efficiency perovskite solar cells is typically complex, requiring the sequential deposition of a charge-blocking layer, a perovskite absorber layer, an interface charge transport layer, and an electrode layer. Shortening the fabrication process without sacrificing efficiency would help reduce process complexity and manufacturing costs, thereby improving the large-scale mass production of perovskite solar cells.

[0004] In inverted perovskite solar cells without a hole transport layer, p-type additives such as 2,3,5,6-tetrafluoro-7,7,8,8-tetracyano-p-quinone dimethyl fluoride, fluorinated (tetraarylbenzo[1,2-b:4,5-b']dipyrrole-1,5-diethylenedialkyl)dialkylsulfonate, and [4-(3,6-dimethyl-9H-carbazole-9-yl)butyl]phosphonic acid are typically added to the perovskite precursor solution to eliminate the hole transport layer deposition step. The aim is to modify the energy level arrangement at the transparent conductive oxide / perovskite interface. However, the efficiency and stability of these hole transport layer-free perovskite solar cells lag far behind those of conventional structured cells. Furthermore, conventional p-type dopants are prone to degradation under photothermal conditions, leading to numerous deep-level traps in the perovskite film, reducing the lattice stability of the perovskite material, and consequently significantly shortening the long-term lifespan of the perovskite solar cell. Summary of the Invention

[0005] The purpose of this invention is to address the shortcomings of existing technologies by providing a hole-transport layer-free perovskite solar cell based on CuSeCN additive and its preparation method. CuSeCN molecules are extruded from the precursor solution to the perovskite grain boundaries and the bottom of the thin film, achieving P-type doping of the buried interface perovskite thin film, improving the interface hole extraction and transport capabilities, and improving the film quality of the perovskite light-absorbing layer. This significantly improves the efficiency, stability, and process reproducibility of hole-transport layer-free perovskite solar cells.

[0006] To achieve the above objectives, the technical solution adopted by the present invention is as follows: As a first aspect, a perovskite solar cell without a hole transport layer based on CuSeCN additive, wherein the perovskite solar cell comprises, from bottom to top, a transparent conductive substrate layer, a perovskite light-absorbing layer, an electron transport layer, an interface buffer layer, and an electrode layer, wherein the perovskite light-absorbing layer contains CuSeCN additive.

[0007] As a second aspect, the present invention also provides a method for fabricating a hole-transport layer-free perovskite solar cell based on CuSeCN additive, the method comprising the following steps:

[0008] Perovskite powder is dissolved in an organic solvent and stirred until clarified to form a perovskite precursor solution with a concentration of 0.1–3 mol / L. CuSeCN is added and completely dissolved to obtain a perovskite precursor solution containing CuSeCN additive with a concentration of 0.001–50 mg / mL. The perovskite precursor solution containing CuSeCN additive is coated or printed on a clean transparent conductive substrate and heat-treated to obtain a perovskite light-absorbing layer.

[0009] An electron transport layer, an interface buffer layer, and an electrode layer are sequentially deposited on the perovskite light-absorbing layer to obtain a perovskite solar cell based on CuSeCN additive.

[0010] Furthermore, the perovskite has the general structural formula ABX3, where A is selected from Cs. + MA + (CH3NH3 + ), FA + [HC(NH2)NH2 + B is selected from Pb 2+ Sn 2+ 、Ge 2+ X is selected from I - ,Br - Cl - .

[0011] Preferably, the concentration of perovskite in the perovskite precursor solution is 1.6 mol / L; and the concentration of CuSeCN in the perovskite precursor solution containing CuSeCN additive is 7.8 mg / mL.

[0012] Furthermore, the heat treatment temperature of the perovskite light-absorbing layer is 30–300°C, and the time is 5–120 min; preferably, it is treated at 100°C for 30 min.

[0013] Further, the transparent conductive substrate layer is selected from: FTO (fluorine-doped tin oxide) glass, ITO (tin-doped indium oxide) glass, ITO (tin-doped indium oxide) / PET (ethylene terephthalate), ITO (tin-doped indium oxide) / PEN (polyethylene phthalate), and ITO (tin-doped indium oxide) / PI (polyimide); the electron transport layer is fullerene and its derivatives, including: C60, C70, and PC60M; the interface buffer layer is selected from: copper bath, tin oxide, zinc oxide, yttrium oxide, cerium oxide, titanium oxide, and niobium oxide; the electrode layer is selected from: Cu, Ag, Au, Mo, ITO (tin-doped indium oxide), IZO (zinc-doped indium oxide), and AZO (aluminum-doped zinc oxide).

[0014] Preferably, the transparent conductive substrate layer is FTO glass; the electron transport layer is C60; the interface buffer layer is tin oxide; and the electrode layer is IZO.

[0015] Furthermore, the thickness of the perovskite light-absorbing layer containing CuSeCN additive is 100–2000 nm; the thickness of the electron transport layer is 1–100 nm; the thickness of the interface buffer layer is 1–100 nm; and the thickness of the electrode layer is 10–10000 nm.

[0016] Preferably, the thickness of the perovskite light-absorbing layer containing CuSeCN additive is 670 nm; the thickness of the electron transport layer is 20 nm; the thickness of the interface buffer layer is 20 nm; and the thickness of the electrode layer is 460 nm.

[0017] Furthermore, the electron transport layer is deposited by vapor deposition; the interface buffer layer is deposited by vapor deposition, sputtering, reactive plasma deposition, chemical vapor deposition, coating, or printing; the electrode layer is deposited by vapor deposition, sputtering, chemical vapor deposition, coating, or printing.

[0018] Preferably, the electron transport layer is deposited by vapor deposition; the interface buffer layer is deposited by chemical vapor deposition; and the electrode layer is deposited by sputtering deposition.

[0019] Furthermore, the organic solvent used to prepare the perovskite precursor solution is one or more of N,N-dimethylformamide, dimethyl sulfoxide, N-methylpyrrolidone, 2-methoxyethanol, and acetonitrile mixed in any proportion.

[0020] Preferably, the organic solvent used to prepare the perovskite precursor solution is a mixture of acetonitrile, N,N-dimethylformamide and N-methylpyrrolidone in a volume ratio of 3:6:1.

[0021] The beneficial effects of this invention are:

[0022] 1. In this invention, CuSeCN is added to the perovskite precursor solution. On the one hand, SeCN... - and Pb 2+ The strong coordination between the perovskite precursors induces micro-clustering, promoting heterogeneous nucleation and preferred orientation growth of the perovskite crystals, leading to an increase in the average grain size of the perovskite film. On the other hand, selenium and copper atoms in CuSeCN interact with uncoordinated Pb atoms on the surface. 2+ and the suspended I - Strong bonding forms a local hole-collecting contact structure with good passivation effect, reducing non-radiative recombination, inhibiting perovskite phase separation, and enhancing the chemical structural stability of perovskite films.

[0023] 2. The CuSeCN additive molecules used in this invention effectively fill the vacancies at the grain boundaries of the perovskite thin film, leading to a decrease in the electron donor state density and an increase in the hole concentration, thus achieving good P-type doping of the bottom perovskite film. Simultaneously, the band bending at the CuSeCN-doped perovskite interface forms good hole-selective contact, promoting effective hole extraction and transfer, eliminating the interfacial band barrier, releasing residual stress in the perovskite thin film, and improving the device's efficiency and stability.

[0024] 3. The perovskite solar cells regulated by CuSeCN additives in this invention have advantages such as simple fabrication process, high photoelectric conversion efficiency, good long-term working stability, and high reproducibility of preparation. Attached Figure Description

[0025] The present invention will be further described below with reference to the accompanying drawings and embodiments;

[0026] Figure 1 This is a schematic diagram of the perovskite solar cell structure based on CuSeCN additive of the present invention;

[0027] Figure 2 The images show SEM images of the perovskite absorbing layer with and without CuSeCN additive of the present invention; wherein, (a) is the SEM image of the perovskite absorbing layer without additive; (b) is the SEM image of the perovskite absorbing layer with CuSeCN additive; (c) is the SEM image of the perovskite absorbing layer with CuSCN additive; and (d) is the SEM image of the perovskite absorbing layer with Me-4PACz additive.

[0028] Figure 3 This is the transient fluorescence spectrum of the perovskite absorbing layer with and without CuSeCN additive according to the present invention;

[0029] Figure 4 This is a graph showing the relationship between the efficiency of the hole transport layer-free perovskite solar cell with CuSeCN additive of the present invention and the storage time of the perovskite precursor solution.

[0030] In the figure: 1. Transparent conductive substrate; 2. Perovskite light-absorbing layer; 3. Electron transport layer; 4. Interface buffer layer; 5. Electrode layer; 6. CuSeCN additive. Detailed Implementation

[0031] The principles and features of the present invention are described below in conjunction with the accompanying drawings. The examples given are for illustrative purposes only and are not intended to limit the scope of the invention.

[0032] The idea behind this invention is to effectively p-type dope the lower interface perovskite film using CuSeCN additive, where SeCN in CuSeCN... - With uncoordinated Pb 2+ Strong bonds are formed at the grain boundaries of the perovskite thin film, enabling it to act as an electron acceptor and facilitating the transition of the bottom perovskite's conductivity from n-type to p-type. Simultaneously, the introduction of CuSeCN effectively regulates the perovskite crystallization kinetics, increasing the perovskite grain size, releasing the tensile stress in the bottom perovskite lattice, and forming a charge transport interface with low defect state density, thus achieving a highly efficient and stable perovskite solar cell without a hole transport layer.

[0033] Example 1:

[0034] like Figure 1 As shown, a perovskite solar cell without a hole transport layer based on CuSeCN additive and its fabrication method include the following steps:

[0035] Step 1: The steps for synthesizing CuSeCN:

[0036] 25.0 g (100 mmol) of CuSO4·5H2O was dissolved in 500 mL of deionized water. Then, 25.0 g (100 mmol) of Na2S2O3·5H2O was added to the solution, and the mixture was stirred continuously to obtain a dark green solution. The solution was cooled to 0 °C, and then 9.7 g (67 mmol) of KSeCN aqueous solution was added dropwise. A blue-black precipitate initially formed, and after stirring for 40 minutes, the precipitate turned white. Finally, the white solid was filtered and washed twice successively with water, ethanol, and ether. After vacuum drying at 70 °C for 12 hours, a grayish-white CuSeCN powder (10 g, yield 89%) was obtained.

[0037] Step 2: The steps for fabricating a hole-transport layer-free perovskite solar cell containing CuSeCN additive:

[0038] (1) The FTO glass was ultrasonically cleaned sequentially with glass cleaning agent, ultrapure water and alcohol, and dried after cleaning to obtain a clean FTO glass substrate.

[0039] (2) First, weigh CsI, MAI, FAI, and PbI2 powder (molar ratio of 0.1:0.1:0.8:1.08) and dissolve them in a mixed solvent of acetonitrile, N,N-dimethylformamide, and N-methylpyrrolidone in a volume ratio of 3:6:1. After stirring and clarifying, a 1.6 mol / L perovskite precursor solution is obtained. Then, weigh 7.8 mg CuSeCN and add it to 1 mL of the perovskite precursor solution. After stirring and dissolving completely, a perovskite precursor solution containing CuSeCN additive is obtained.

[0040] (3) A perovskite precursor solution containing CuSeCN additive was slit-coated on a clean FTO glass substrate, and the coated perovskite wet film was heat-treated at 100°C for 30 min to obtain a perovskite light-absorbing layer with a thickness of 670 nm.

[0041] (4) A 20 nm thick C60 electron transport layer, a 20 nm thick tin oxide interface buffer layer, and a 460 nm thick IZO electrode layer are sequentially deposited on the perovskite light-absorbing layer to obtain a hole-transport layer-free perovskite solar cell based on CuSeCN additive.

[0042] Comparative Example 1:

[0043] A perovskite solar cell without a hole transport layer and without CuSeCN additive, and its fabrication method, comprising the following steps:

[0044] (1) The FTO glass was ultrasonically cleaned sequentially with glass cleaning agent, ultrapure water and alcohol, and dried after cleaning to obtain a clean FTO glass substrate.

[0045] (2) First, weigh CsI, MAI, FAI, and PbI2 powder (molar ratio of 0.1:0.1:0.8:1.08) and dissolve them in a mixed solvent of acetonitrile, N,N-dimethylformamide, and N-methylpyrrolidone in a volume ratio of 3:6:1. After stirring and clarifying, a 1.6 mol / L perovskite precursor solution is obtained. After stirring and dissolving completely, a perovskite precursor solution without CuSeCN additive is obtained.

[0046] (3) A perovskite precursor solution was slit-coated on a clean FTO glass substrate, and the coated perovskite wet film was heat-treated at 100°C for 30 min to obtain a perovskite light-absorbing layer with a thickness of 670 nm.

[0047] (4) A 20 nm thick C60 electron transport layer, a 20 nm thick tin oxide interface buffer layer, and a 460 nm thick IZO electrode layer are sequentially deposited on the perovskite light-absorbing layer to obtain a perovskite solar cell without CuSeCN additives and without a hole transport layer.

[0048] Comparative Example 2:

[0049] A perovskite solar cell without a hole transport layer based on CuSCN additive and its fabrication method, comprising the following steps:

[0050] (1) The FTO glass was ultrasonically cleaned sequentially with glass cleaning agent, ultrapure water and alcohol, and dried after cleaning to obtain a clean FTO glass substrate.

[0051] (2) First, weigh CsI, MAI, FAI, and PbI2 powder (molar ratio of 0.1:0.1:0.8:1.08) and dissolve them in a mixed solvent of acetonitrile, N,N-dimethylformamide, and N-methylpyrrolidone in a volume ratio of 3:6:1. After stirring and clarifying, a 1.6 mol / L perovskite precursor solution is obtained. Then, weigh 11.7 mg CuSCN and add it to 1 mL of the perovskite precursor solution. After stirring and dissolving completely, a perovskite precursor solution containing CuSCN additive is obtained.

[0052] (3) A perovskite precursor solution containing CuSCN additive is slit-coated on a clean FTO glass substrate. The coated perovskite wet film is heat-treated at 100°C for 30 min to obtain a perovskite light-absorbing layer with a thickness of 670 nm.

[0053] (4) A 20 nm thick C60 electron transport layer, a 20 nm thick tin oxide interface buffer layer, and a 460 nm thick IZO electrode layer are sequentially deposited on the perovskite light-absorbing layer to obtain a hole transport layer-free perovskite solar cell based on CuSCN additive.

[0054] Comparative Example 3:

[0055] A hole-transport layer-free perovskite solar cell based on [4-(3,6-dimethyl-9H-carbazole-9-yl)butyl]phosphonic acid (Me-4PACz) additive and its preparation method, comprising the following steps:

[0056] (1) The FTO glass was ultrasonically cleaned sequentially with glass cleaning agent, ultrapure water and alcohol, and dried after cleaning to obtain a clean FTO glass substrate.

[0057] (2) First, weigh CsI, MAI, FAI, and PbI2 powder (molar ratio of 0.1:0.1:0.8:1.08) and dissolve them in a mixed solvent of acetonitrile, N,N-dimethylformamide, and N-methylpyrrolidone in a volume ratio of 3:6:1. After stirring and clarifying, a 1.6 mol / L perovskite precursor solution is obtained. Then, weigh 3.2 mg Me-4PACz and add it to 1 mL of the perovskite precursor solution. After stirring and dissolving completely, a perovskite precursor solution containing Me-4PACz additive is obtained.

[0058] (3) A perovskite precursor solution containing Me-4PACz additive was slit-coated on a clean FTO glass substrate. The coated perovskite wet film was heat-treated at 100°C for 30 min to obtain a perovskite light-absorbing layer with a thickness of 670 nm.

[0059] (4) A 20 nm thick C60 electron transport layer, a 20 nm thick tin oxide interface buffer layer, and a 460 nm thick IZO electrode layer are sequentially deposited on the perovskite light-absorbing layer to obtain a hole transport layer-free perovskite solar cell based on Me-4PACz additive.

[0060] Comparative Example 4:

[0061] A perovskite solar cell based on a CuSeCN hole transport layer and its fabrication method, comprising the following steps:

[0062] Step 1: The steps for synthesizing CuSeCN:

[0063] 25.0 g (100 mmol) of CuSO4·5H2O was dissolved in 500 mL of deionized water. Then, 25.0 g (100 mmol) of Na2S2O3·5H2O was added to the solution, and the mixture was stirred continuously to obtain a dark green solution. The solution was cooled to 0 °C, and then 9.7 g (67 mmol) of KSeCN aqueous solution was added dropwise. A blue-black precipitate initially formed, and after stirring for 40 minutes, the precipitate turned white. Finally, the white solid was filtered and washed twice successively with water, ethanol, and ether. After vacuum drying at 70 °C for 12 hours, a grayish-white CuSeCN powder (10 g, yield 89%) was obtained.

[0064] Step 2: Fabrication of perovskite solar cells based on CuSeCN hole transport layers:

[0065] (1) The FTO glass was ultrasonically cleaned sequentially with glass cleaning agent, ultrapure water and alcohol, and dried after cleaning to obtain a clean FTO glass substrate.

[0066] (2) Weigh CuSeCN and dissolve it in a mixed solvent of water:ethanolamine:ethylenediamine:diethanolamine in a volume ratio of 2:6:1:1 to form a 20 mg / mL CuSeCN solution. Coat the CuSeCN solution in a slit on a clean FTO glass substrate. After coating, heat treat at 300℃ for 30 min to obtain a 25 nm CuSeCN hole transport layer.

[0067] (3) First, weigh CsI, MAI, FAI, and PbI2 (molar ratio of 0.1:0.1:0.8:1.08) powder and dissolve them in a mixed solvent of acetonitrile, N,N-dimethylformamide and N-methylpyrrolidone in a volume ratio of 3:6:1. After stirring and clarifying, a 1.6 mol / L perovskite precursor solution is obtained. After stirring and dissolving completely, a perovskite precursor solution is obtained.

[0068] (4) A perovskite precursor solution was slit-coated on an FTO glass substrate covered with a CuSeCN hole transport layer. The coated perovskite wet film was heat-treated at 100°C for 30 min to obtain a perovskite light-absorbing layer with a thickness of 670 nm.

[0069] (5) A 20 nm thick C60 electron transport layer, a 20 nm thick tin oxide interface buffer layer, and a 460 nm thick IZO electrode layer are sequentially deposited on the perovskite light-absorbing layer to obtain a perovskite solar cell based on the CuSeCN hole transport layer.

[0070] As shown in Table 1, the perovskite solar cell without a hole transport layer prepared with CuSeCN additive has a photoelectric conversion efficiency of up to 24.95%, and the efficiency only decreases by 2.1% after 1000 hours of maximum power point tracking. The device efficiency and stability are far superior to other comparative devices, indicating that the addition of CuSeCN to the perovskite precursor solution can achieve effective doping of the bottom perovskite by CuSeCN, induce rapid heterogeneous nucleation of perovskite, improve the crystal quality of perovskite film, eliminate buried interface defect recombination centers, extend the interface carrier transport lifetime, and simultaneously improve the efficiency and stability of perovskite cell.

[0071] Table 1. Performance parameters of devices in the examples and comparative examples

[0072]

[0073] like Figure 2 As shown, the perovskite thin films prepared with CuSeCN additive perovskite precursor solutions have large grain size and high crystallinity, and CuSeCN molecules can be effectively enriched at the grain boundaries of the thin films.

[0074] like Figure 3 As shown, the perovskite light-absorbing layer containing CuSeCN additive exhibits an ultralong transient fluorescence lifetime, indicating that the addition of CuSeCN can eliminate defect-induced charge recombination centers in the perovskite film, suppress nonradiative recombination of charge carriers in the film, and increase the carrier diffusion length.

[0075] like Figure 4As shown, the perovskite precursor solution with CuSeCN additive also exhibits excellent solution storage stability. Even with a perovskite precursor solution that has been stored for 3 weeks, device performance comparable to that of a fresh perovskite solution can still be fabricated. This significantly improves the consistency of the fabrication process for perovskite solar cells without a hole transport layer and provides a strong guarantee for the mass production of perovskite solar cells.

[0076] Finally, combining Figure 2-4 As shown, the addition of CuSeCN causes the energy band at the anode interface between perovskite and transparent conductive oxide to bend upwards, and the maximum value of the perovskite valence band becomes shallower, forming a perovskite / anode interface with energy level matching. This enables the extraction of holes from within the perovskite and efficient transport to the anode without relying on a hole transport layer, improving the film quality of the perovskite film and reducing charge recombination within the perovskite film. This results in the fabrication of a highly efficient and stable perovskite solar cell without a hole transport layer, significantly simplifying the cell fabrication process, reducing cell manufacturing costs, and promoting the industrialization of perovskite solar cells.

[0077] The above description is merely a preferred experimental example of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of the present invention should be included within the protection scope of the present invention.

Claims

1. A perovskite solar cell without a hole transport layer based on CuSeCN additive, characterized in that, The perovskite solar cell consists of, from bottom to top, a transparent conductive substrate layer, a perovskite light-absorbing layer, an electron transport layer, an interface buffer layer, and an electrode layer, wherein the perovskite light-absorbing layer contains CuSeCN additive.

2. A method for fabricating a hole-transport layer-free perovskite solar cell based on CuSeCN additive, characterized in that, The method for fabricating the perovskite solar cell includes the following steps: Perovskite powder is dissolved in an organic solvent and stirred until clarified to form a perovskite precursor solution with a concentration of 0.1–3 mol / L. CuSeCN is added and dissolved completely to obtain a perovskite precursor solution containing CuSeCN additive with a concentration of 0.001–50 mg / mL. The perovskite precursor solution containing CuSeCN additive is coated onto a clean, transparent conductive substrate and heat-treated to obtain a perovskite light-absorbing layer. An electron transport layer, an interface buffer layer, and an electrode layer are sequentially deposited on the perovskite light-absorbing layer to obtain a perovskite solar cell based on CuSeCN additive.

3. The method for preparing a hole-transport layer-free perovskite solar cell based on CuSeCN additive as described in claim 2, characterized in that, The perovskite has the general structural formula ABX3, where A is selected from Cs+, MA+, FA+, B is selected from Pb2+, Sn2+, Ge2+, and X is selected from I-, Br-, Cl-.

4. The method for fabricating a hole-transport layer-free perovskite solar cell based on CuSeCN additive as described in claim 2, characterized in that, The heat treatment temperature of the perovskite light-absorbing layer is 30–300 °C, and the time is 5–120 min.

5. The method for preparing a hole-transport layer-free perovskite solar cell based on CuSeCN additive as described in claim 2, characterized in that, The transparent conductive substrate layer is selected from: FTO glass, ITO glass, ITO / PET, ITO / PEN, ITO / PI; the electron transport layer is fullerene and / or its derivatives, selected from: C60, C70, PC60M; the interface buffer layer is selected from: copper bath, tin oxide, zinc oxide, yttrium oxide, cerium oxide, titanium oxide, niobium oxide; the electrode layer is selected from: Cu, Ag, Au, Mo, ITO, IZO, AZO.

6. The method for fabricating a hole-transport layer-free perovskite solar cell based on CuSeCN additive as described in claim 2, characterized in that, The thickness of the perovskite light-absorbing layer containing CuSeCN additive is 100–2000 nm; the thickness of the electron transport layer is 1–100 nm; the thickness of the interface buffer layer is 1–100 nm; and the thickness of the electrode layer is 10–10000 nm.

7. The method for preparing a hole-transport layer-free perovskite solar cell based on CuSeCN additive as described in claim 2, characterized in that, The electron transport layer is deposited by vapor deposition; the interface buffer layer is deposited by vapor deposition, sputtering, reactive plasma deposition, chemical vapor deposition, or coating; the electrode layer is deposited by vapor deposition, sputtering, chemical vapor deposition, or coating.

8. The method for fabricating a hole-transport layer-free perovskite solar cell based on CuSeCN additive as described in any one of claims 5-7, characterized in that, The transparent conductive substrate is FTO glass; the electron transport layer is C60; the interface buffer layer is tin oxide; the electrode layer is IZO; the thickness of the perovskite light-absorbing layer containing CuSeCN additive is 670 nm; the thickness of the electron transport layer is 20 nm; the thickness of the interface buffer layer is 20 nm; the thickness of the electrode layer is 460 nm; the electron transport layer is deposited by vapor deposition; the interface buffer layer is deposited by chemical vapor deposition; and the electrode layer is deposited by sputtering deposition.

9. The method for preparing a hole-transport layer-free perovskite solar cell based on CuSeCN additive as described in claim 2, characterized in that, The organic solvent used to prepare the perovskite precursor solution is one or more of N,N-dimethylformamide, dimethyl sulfoxide, N-methylpyrrolidone, 2-methoxyethanol, and acetonitrile.

10. The method for fabricating a hole-transport layer-free perovskite solar cell based on CuSeCN additive as described in claim 2 or 9, characterized in that, The concentration of perovskite in the perovskite precursor solution is 1.6 mol / L; the concentration of CuSeCN in the perovskite precursor solution containing CuSeCN additive is 7.8 mg / mL; the organic solvent used to prepare the perovskite precursor solution is a mixture of acetonitrile, N,N-dimethylformamide and N-methylpyrrolidone in a volume ratio of 3:6:1.

Citation Information

Patent Citations

  • Functionalized perovskite material based on novel ionic liquid and application of functionalized perovskite material in solar cell preparing

    CN107337644A

  • Perovskite precursor solution, perovskite solar cell and preparation method

    CN118742174A